Keith Haring, Jean-Michel Basquiat - crossing lines - Buchhart, Dieter 1971-; Hofbauer, Anna Karina 1973-; Yablonsky, Linda 1948-; Holzer, Jenny 1950-; Condo, George 1957-; Cortez, Diego; Astor, Patti; Warsh, Larry; Russell-Cook, Myles; Montez, Ricardo 1975-; Ricard, Rene 1946-2014; Wiedmann, Anke 1984- (National Gallery of Victoria, 2020)
"Keith Haring and Jean-Michel Basquiat are considered icons of twentieth-century art. Both are known for their idiosyncratic imagery, radical viewpoints and complex socio-political commentary, and both employed signs, symbols and words to explore ideas around race, sexuality, spirituality and other aspects of contemporary life. Keith Haring, Jean-Michel Basquiat: Crossing Lines draws out the many intersections between the artists' lives, practices and ideas. It includes more than 200 images, including works created in public spaces, paintings, sculptures, objects, works on paper and photographs, which are accompanied by new essays and interviews. Keith Haring, Jean-Michel Basquiat: Crossing Lines is a record of and a tribute to the work of two boundary-pushing, highly influential artists"--Publisher website
Exhibition held at the National Gallery of Victoria, Melbourne, 1 December 2019 - 13 April 2020
Keywords: Basquiat, Jean Michel -- 1960-1988; Haring, Keith -- 1958-1990; Kunst; Art, American -- 20th century -- Criticism and interpretation; Haring, Keith; Haring, Keith -- Criticism and interpretation; Basquiat, Jean-Michel, 1960-1988; Basquiat, Jean-Michel, 1960-1988 -- Criticism and interpretation; National Gallery of Victoria; Haring, Keith / Exhibitions; Haring, Keith / Criticism and interpretation; Basquiat, Jean-Michel / 1960-1988 / Exhibitions; Basquiat, Jean-Michel / 1960-1988 / Criticism and interpretation; Art, American / 20th century / Exhibitions; Haring, Keith / 1958-1990 / Expositions; Basquiat, Jean Michel / 1960-1988 / Expositions; Art américain / 20e siècle / Expositions; Basquiat, Jean-Michel / 1960-1988; Art, American; 1900-1999; Criticism, interpretation, etc; Exhibition catalogs; Ausstellungskatalog -- National Gallery of Victoria -- 01.12.2019-13.04.2020 -- Melbourne; Bildband